2016
DOI: 10.1039/c6ra15661d
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/nickel aerogel: an effective catalyst for the thermal decomposition of ammonium perchlorate

Abstract: G/Ni aerogels were prepared by a sol–gel method and supercritical CO2 drying. They exhibit a remarkable catalytic performance for the thermal decomposition of AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…125 Owing to the synergistic effect of the spinel-structured copper chromite nanoparticles, high-surface area of GA and composite processing of AP, the HTD peak of AP decreased from 432 to 323 C with CuCr 2 O 4 @GA contents of 4 wt%. Lan et al 124 obtained graphene/nickel (G/Ni) aerogels by sol-gel method and supercritical CO 2 drying technology. Micromorphology analysis shows that G/Ni aerogel has mesoporous structure and large specific surface area, and Ni nanoparticles are uniformly distributed on the microstructure of GA (Figure 12(c),(d)).…”
Section: Graphene Aerogelmentioning
confidence: 99%
“…125 Owing to the synergistic effect of the spinel-structured copper chromite nanoparticles, high-surface area of GA and composite processing of AP, the HTD peak of AP decreased from 432 to 323 C with CuCr 2 O 4 @GA contents of 4 wt%. Lan et al 124 obtained graphene/nickel (G/Ni) aerogels by sol-gel method and supercritical CO 2 drying technology. Micromorphology analysis shows that G/Ni aerogel has mesoporous structure and large specific surface area, and Ni nanoparticles are uniformly distributed on the microstructure of GA (Figure 12(c),(d)).…”
Section: Graphene Aerogelmentioning
confidence: 99%
“…The thermal decomposition of AP is easily affected by the catalysts, and previous studies have demonstrated that the Fe 2 O 3 nanoparticles as a nanoscale catalyst are confirmed to be pretty effective on the thermal decomposition of AP because of its nanoscale dimensions and high surface activity. However, pure nanosized Fe 2 O 3 particles are prone to aggregate, resulting in fewer active site exposure which can inhibit catalytic activity toward AP . For example, Abhijit Dey et al studied the AP decomposition temperature change between pure AP and AP with the catalyst, the results of which showed that there is almost no improvement even with the addition of nano-Fe 2 O 3 , so a nonuniform dispersion of Fe 2 O 3 nanoparticles originated from agglomeration will seriously restrict their accessible surface area, leading to a decreased catalytic efficiency in reactions . A reliable way to solve this problem is to anchor the Fe 2 O 3 nanoparticles onto a support to preclude agglomeration and GO, which could be a good supporting material because of its high specific surface area .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Abhijit Dey et al studied the AP decomposition temperature change between pure AP and AP with the catalyst, the results of which showed that there is almost no improvement even with the addition of nano-Fe 2 O 3 , so a nonuniform dispersion of Fe 2 O 3 nanoparticles originated from agglomeration will seriously restrict their accessible surface area, leading to a decreased catalytic efficiency in reactions . A reliable way to solve this problem is to anchor the Fe 2 O 3 nanoparticles onto a support to preclude agglomeration and GO, which could be a good supporting material because of its high specific surface area . It is indicated from publications that the integration of GO and Fe 2 O 3 nanoparticles can result in an improved catalytic performance in the field of catalysis via the hydrothermal synthesis method. , Unlike the hydrothermal synthesis process, vacuum-freeze-drying, also called lyophilization, begins by rapidly freezing the substance with liquid nitrogen, so the liquid-state material is changed to solid state immediately, and frozen water will subsequently be removed by sublimation because of low temperature and high vacuum atmosphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…rGO OPD and rGO PXDA aerogels showed a weak broad peak at 2θ = 26.7 • and 26.4 • respectively, which attributed to graphitic structure (d = 0.34 nm). The other aerogels showed very weak broad graphite (002) peaks with 2θ = 21−24 • , which corresponds to an interlayer spacing of 0.43-0.36 nm and is due to disordered stacking of the reduced graphene sheets (Bourlinos et al, 2003;Chen et al, 2013;Fan et al, 2013;Hu et al, 2013;Lan et al, 2016).…”
Section: Tg Analysismentioning
confidence: 99%